Incidence of hypothermia in critically ill patients receiving continuous renal replacement therapy in Siriraj Hospital in Siriraj Hospital, Thailand - Thonnarat Pornsirirat; Nualnapa Kasemvilawan; Patcharavalia Pattanacharoenwong; Saisunee Arpibanwana; Hatairat Kondon; Thummaporn Naorungroj (Acute and Critical Care)
Background Hypothermia is a relatively common complication in patients receiving continuous renal replacement therapy (CRRT). However, few studies have reported the factors associated with hypothermia. Methods A retrospective cohort study was performed in five intensive care units (ICUs) to evaluate the incidence of hypothermia and the predictive factors for developing hypothermia during CRRT, with hypothermia defined as a time-weighted average temperature <36 °C. Results From January 2020 to December 2021, 300 patients were enrolled. Hypothermia developed in 23.7% of them within the first 24 hours after CRRT initiation. Compared to non-hypothermic patients, hypothermic patients were older and had lower body weight, more frequent acidemia, and higher ICU and 30-day mortality rates. In the multivariate analysis, age >70 years (odds ratio [OR], 2.59; 95% CI, 1.38–4.98; P=0.004), higher positive fluid balance on the day before CRRT (OR, 1.11; 95% CI, 1.02–1.22; P=0.02), and CRRT dose (OR, 1.003; 95% CI, 1.00–1.01; P=0.04) were significantly associated with hypothermia. Conversely, a higher body weight was independently associated with mitigated risk of hypothermia (OR, 0.89; 95% CI, 0.81–0.97; P=0.01). Moreover, a higher coefficient of variance of temperature was associated with greater ICU mortality (OR, 1.41; 95% CI, 1.13–1.78; P=0.003). Conclusion Hypothermia during CRRT is a relatively common occurrence, and factors associated with hypothermia onset in the first 24 hours include older age, lower body weight, higher positive fluid balance on the day before CRRT, and higher CRRT dose. Greater temperature variability was associated with increased ICU mortality.